Upregulated GABA Inhibitory Function in ADHD Children with Child Behavior Checklist–Dysregulation Profile: 123I-Iomazenil SPECT Study - Nagamitsu, Shinichiro; Yamashita, Yushiro; Tanigawa, Hitoshi; Chiba, Hiromi; Kaida, Hayato; Ishibashi, Masatoshi; Kakuma, Tatsuyuki; Croarkin, Paul E.; Matsuishi, Toyojiro (Frontiers in Psychiatry, 2015)
The Child Behavior Checklist–Dysregulation Profile (CBCL-DP) refers to a pattern of elevated scores on the Attention Problems, Aggression, and Anxiety/Depression subscales of the Child Behavior Checklist. The aim of the present study was to investigate the potential role of GABA inhibitory neurons in children with attention deficit/hyperactivity disorder (AD/HD) and dysregulation assessed with a dimensional measure. Brain single photon emission computed tomography (SPECT) was performed in 35 children with AD/HD using 123I-iomazenil, which binds with high affinity to benzodiazepine receptors. Iomazenil binding activities were assessed with respect to the presence or absence of a threshold CBCL-DP (a score ≥210 for the sum of the three subscales Attention Problems, Aggression, and Anxiety/Depression). We then attempted to identify which CBCL-DP subscale explained the most variance with respect to SPECT data, using “age”, “sex”, and “history of maltreatment” as covariates. Significantly higher iomazenil binding activity was seen in the posterior cingulate cortex (PCC) of AD/HD children with a significant CBCL-DP. The Anxiety/Depression subscale on the CBCL had significant effects on higher iomazenil binding activity in the left superior frontal, middle frontal, and temporal regions, as well as in the PCC. The present brain SPECT findings suggest that GABAergic inhibitory neurons may play an important role in the neurobiology of the CBCL-DP, in children with ADHD.